Ketimpangan Ekonomi, Kemiskinan dan Akses Informasi : Bagaimana Pengaruhnya Terhadap Kriminalitas ? - Andi Ahmad Mardinsyah; Ni Made Sukartini (Jurnal Ekonika : Jurnal Ekonomi Universitas Kadiri, 2020)
This study aims to assess the linkage between inequality and information access concerning criminal acts in Indonesia. Macro-level data of 33 provinces in Indonesia during 2012-2017 from the Central Statistics Agency (BPS) were analyzed using panel data regression methods. The analysis affirms that Fixed Effect Model (FEM) is the most appropriate model in explaining criminal behavior. Interestingly, poverty reduction leads in increasing crime activity. There is not enough evidence that inequality and information access influence crime. It is necessary to reconsider the use of microdata to determine the effect of inequality and access to information on crime.